Film Studies of New Aromatic-Aliphatic Polyimides - RAJENDIRAN, T.V.; LAKSHMI, L. (Asian Journal of Chemistry, 2010)
Three new aromatic-aliphatic polyimides based on 3,3',4,4'- azobenzene tetracarboxylic dianhydride and the aliphatic diamines viz., ethylene diamine, 1,4-butane diamine and 1,8-octane diamine were synthesized and the films were cast. Film studies were carried out by scanning electron microscope, dielectric constant, microwave and X-ray diffraction pattern. The results were correlated with structure and orientation of the molecules.